PEMBUATAN RADIO ONLINE DENGAN AUDIO STREAMING DAN VIRTUAL PRIVATE SERVER UNTUK KOMUNITAS BLOGER SEMARANG LOENPIA.NET - Mohammad Sani Suprayogi (Jurusan Teknologi Informasi Universitas Semarang, 2012)
Information technology, especially in terms of audio processing has been greatly expanded, with the use of Internet and webtechnologies are able to deliver the audio data to the entire world. That Audio Streaming, a service that can be used by anyone todisseminate information. Conventional radios have limited range and frequency of broadcasts. Utilizing Audio Streaming, OnlineRadio we can make that can be heard from around the world. A device that takes more simple that anyone can create and take advantage of this technology.This research proves that by using VPS, Linux, Internet, and Website. Anyone can make OnlineRadio easily and used for any purpose.